Effect of heavy metal pollution on mineralization of soil particulate organic matters and added plant materials - WANG Li-ping; ZHENG Shun-an; ZHANG Ming-kui (浙江大学学报. 农业与生命科学版, 2008)
In order to understand the effect of heavy metal pollution on mineralization of soil organic matter and added plant materials, incubation experiments were conducted to study dynamics of mineralization and accumulation of particulate organic matter (POM) and microbial biomass C in three soils amended with three different plant materials. The tested soils and plant materials contained different levels of heavy metals. The results show that the high concentration of heavy metals accumulated in polluted soils slowed down the rate of C mineralization of the POM and added plant materials, enhanced the capacity of the POM resistant to biodegradation, and thus increased accumulation of particulate organic matter. The microbial biomass C of the soils decreased with increasing the pollution degree of heavy metals of the soils. When soils were amended with low heavy metals-contained plant material, medium accumulation of heavy metals in the soils could increase the intensity of CO2 respiration. The accumulation of the POM increased with increasing accumulation of heavy metals in the soils and plant materials. The heavy metal pollution of the plant materials had greater effects on accumulation of the POM than that of the soils. The results found that heavy metals were significantly enriched in the particulate organic matter. The enrichment is linked to the declined rate of organic matter mineralization and the increased stability of the POM in the soils.